The Correlation Between Neurologic Findings And DXA in Mechanical Low Back Pain and/or Leg Pain - Halil Koyuncu; Meryem Gül Erden; Neval Bozok Arat (Galenos Yayinevi, 2012)
Aim: Mechanical problems are frequently encountered and may cause low back pain (LBP) and leg pain by pressure on nerve roots. Neurologic findings like decreased deep tendon reflexes may be found during the physical examination. There are many etiologic factors in the pathogenesis of LBP and metabolic bone diseases like osteoporosis and osteomalacia also may cause mecanical LBP. Materials and Methods: In this study, 25 patients between 30-65 years were evaluated. In the patients, sensorial changes, deep tendon reflexes and muscle strength were correlated with dual x-ray absorbsiometry (DXA) results. Demographic findings (age, sex, occupation, education) and clinical results (pain duration, pain severity, height, weight) were evaluated. In DXA evaluation, L1-L4 total, femur neck and femur total bone mineral density (BMD) and T-scores were reported. Results: Pain severity, according to visual analog scale (VAS) was higher than six. Muscle strength, sensation and deep tendon reflex averages were found to be normal. DXA results were found to be osteopenic in femoral neck region of our patients. DXA results and clinical findings showed a weak and negative statistically significant correlation only between BMD at L1-L4 and pain severity. Conclusion: This study should be performed comparatively, multicenter, in a larger number of patients with LBP, for a longer period of follow-up. (Turkish Journal of Osteoporosis 2012;18:19-23)